Configuration of Multifunctional Polyimide/Graphene/Fe3O4 Hybrid Aerogel-Based Phase-Change Composite Films for Electromagnetic and Infrared Bi-Stealth - Tao Shi; Zhiheng Zheng; Huan Liu; Dezhen Wu; Xiaodong Wang (Nanomaterials, 2021)
Electromagnetic (EM) and infrared (IR) stealth play an important role in the development of military technology and the defense industry. This study focused on developing a new type of multifunctional composite film based on polyimide (PI)/graphene/Fe3O4 hybrid aerogel and polyethylene glycol (PEG) as a phase change material (PCM) for EM and IR bi-stealth applications. The composite films were successfully fabricated by constructing a series of PI-based hybrid aerogels containing different contents of graphene nanosheets and Fe3O4 nanoparticles through prepolymerizaton, film casting, freeze-drying, and thermal imidization, followed by loading molten PEG through vacuum impregnation. The construction of PI/graphene/Fe3O4 hybrid aerogel films provides a robust, flexible, and microwave-absorption-functionalized support material for PEG. The resultant multifunctional composite films not only exhibit high microwave absorption effectiveness across a broad frequency range, but also show a good ability to implement thermal management and temperature regulation under a high latent-heat capacity of over 158 J/g. Most of all, the multifunctional composite films present a wideband absorption capability at 7.0–16.5 GHz and a minimum reflection loss of −38.5 dB. This results in excellent EM and IR bi-stealth performance through the effective wideband microwave absorption of graphene/Fe3O4 component and the thermal buffer of PEG. This study offers a new strategy for the design and development of high-performance and lightweight EM–IR bi-stealth materials to meet the requirement of stealth and camouflage applications in military equipment and defense engineering.